Tecnología del aprendizaje y del conocimiento (TAC), para la enseñanza aprendizaje de Ciencias Naturales, sexto grado, Escuela Alonso de Mercadillo, 2024 - 2025 - Torres Orellana, Katty Jazmin (2025)
For learning to be meaningful, it is essential to incorporate innovative methodologies that effectively support the teaching and learning process. Consequently, Tecnologías del Aprendizaje y del Conocimiento (TAC) fundamentally fosters dynamic and active educational experiences. The primary objective of this research was to analyze the impact of TAC on the teaching-learning process of Natural Sciences among sixth-grade students at Alonso de Mercadillo School during the 2024–2025 academic period. Three specific objectives guided the study: (1) diagnose the main learning challenges faced by students in Natural Sciences, (2) identify TAC resources utilized by teachers to support teaching and learning, and (3) develop a didactic proposal leveraging TAC to enhance the teaching-learning process in Natural Sciences. This research employed a mixed methods approach with a descriptive and nonexperimental design, enabling observation and description of the study variables without manipulation. Data were collected through an interview and a diagnostic evaluation, utilizing non-probabilistic convenience sampling. The study included the participation of one tutor teacher and 24 sixth-grade students. The results revealed significant barriers to learning, as over 79% of the students scored below the expected level, with grades lower than four. These findings underscore the importance of integrating TAC as a support resource to improve educational processes, foster student engagement, and enhance participation in their learning journey